Verfestigungen in der Interaktion Konstruktionen, sequenzielle Muster, kommunikative Gattungen - Imo, Wolfgang; König, Katharina; Weidner, Beate; Wegner, Lars (Empirische Linguistik / Empirical Linguistics, 2020)
The theoretically and empirically based contributions in this edited volume in honour of Susanne Günther examine different consolidations on the level of interaction. They span from relatively detailed formats such as consolidated practices and actions up to the major forms of communicative genres. It also examines non-verbal routine patterns such as gestures.